Fundamentalism : the search for meaning - Ruthven, Malise (Oxford University Press, 2004)
Fundamentalist movements are seen as the major threat to world peace today, yet 'fundamentalism' is a term that eludes easy definitions. Malise Ruthven, writing with engaging clarity and directness, offers the first book to expose the nature of both religious and secular fundamentalism worldwide and to explore its many forms. - ;Since the end of the Cold War fundamentalism has been seen as the major threat to world peace and prosperity, a concern that was exacerbated by the events of 9/11, and the 'War against Terrorism'. But what does 'fundamentalism' really mean? Since it was coined by Ameri.